2017
DOI: 10.1007/s10404-017-1971-y
|View full text |Cite
|
Sign up to set email alerts
|

Acoustofluidic waveguides for localized control of acoustic wavefront in microfluidics

Abstract: The precise manipulation of acoustic fields in microfluidics is of critical importance for the realization of many biomedical applications. Despite the tremendous efforts devoted to the field of acoustofluidics during recent years, dexterous control, with an arbitrary and complex acoustic wavefront, in a prescribed, microscale region is still out of reach. Here, we introduce the concept of acoustofluidic waveguide, a three-dimensional compact configuration that is capable of locally guiding acoustic waves into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 63 publications
0
21
0
Order By: Relevance
“…Acoustic beams, such as focused, tweezer‐like, and nonparaxial beams, are of interest for a wide range of applications including medical acoustic imaging, nondestructive evaluation, acoustic tweezers, energy harvesting, and wireless energy transfer . Although acoustic beams can be generated using conventional passive metasurfaces, those metasurfaces with fixed configurations lack maneuverability in tuning and reshaping the acoustic beams, once they are designed and fabricated.…”
Section: Resultsmentioning
confidence: 99%
“…Acoustic beams, such as focused, tweezer‐like, and nonparaxial beams, are of interest for a wide range of applications including medical acoustic imaging, nondestructive evaluation, acoustic tweezers, energy harvesting, and wireless energy transfer . Although acoustic beams can be generated using conventional passive metasurfaces, those metasurfaces with fixed configurations lack maneuverability in tuning and reshaping the acoustic beams, once they are designed and fabricated.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, by reducing both the lattice constant and cavity depth, miniaturized PCs could be developed for controlling ultrasonic waves. Such devices could be fabricated by advanced manufacturing techniques, such as replication-based forming [54][55][56] , high-resolution additive manufacturing [57][58][59] , and/or micromilling 60,61 . It should also be possible to reduce the response time of the system through automatic operation.…”
Section: Discussionmentioning
confidence: 99%
“…Micropillar waveguides can also be used to effectively constrain the transducer domain for localized acoustic effects with SAW as the actuation source, where a pillar/post is used to couple acoustic energy to selected microchannel regions 48,[50][51][52] . Rambach et al demonstrated the use of this approach to create particle patterning on top of a waveguide with just a travelling wave 51 , though predictive analytical equations that describe pattern spacings have yet to be developed.…”
Section: Introductionmentioning
confidence: 99%